Metabolism perturbation Caused by the overexpression of carbon monoxide dehydrogenase/Acetyl-CoA synthase gene complex accelerated gas to acetate conversion rate of Eubacterium limosum KIST612. (December 2021) - Kang, Hyunsoo; Park, Byeonghyeok; Oh, Soyoung; Pathiraja, Duleepa; Kim, Ji-Yeon; Jung, Seunghyeon; Jeong, Jiyeong; Cha, Minseok; Park, Zee-Yong; Choi, In-Geol; Chang, In Seop
Highlights: CODH/ACS gene complex overexpressed mutant (ELM031) was constructed. A mutant strain showed increased specific CO oxidation rate by 3.1-fold. Proved a "virtuous cycling" of reducing equivalent is required for CO/CO2 redox. Abstract: Microbial conversion of carbon monoxide (CO) to acetate is a promising upcycling strategy for carbon sequestration. Herein, we demonstrate that CO conversion and acetate production rates of Eubacterium limosum KIST612 strain can be improved by in silico prediction and in vivo assessment. The mimicked CO metabolic model of KIST612 predicted that overexpressing the CO dehydrogenase (CODH) increases CO conversion and acetate production rates. To validate the prediction, we constructed mutant strains overexpressing CODH gene cluster and measured their CO conversion and acetate production rates. A mutant strain (ELM031) co-overexpressing CODH, coenzyme CooC2 and ACS showed a 3.1 × increased specific CO oxidation rate as well as 1.4 × increased specific acetate production rate, compared to the wild type strain. The transcriptional and translational data with redox balance analysis showed that ELM031 has enhanced reducing potential from up-regulation of ferredoxin and related metabolism directly linked to energy conservation.